FEATURES OF THE FUNCTIONING OF THE NATIONAL LABOR MARKET IN CONDITIONS OF MILITARY THREAT AND INTERNAL POPULATION DISPLACEMENT - Liudmyla Akimova; Gаlina Urchik (Соціальна економіка)
The article presents a comprehensive study of the peculiarities of the functioning of the Ukrainian labour market in the context of modern challenges. The objective is to identify existing problems and transform the state policy in the labour market. The study was conducted based on data from the State Employment Service, the online job search portal Work.ua, and various sociological surveys of labour market participants and experts. The results of the analysis demonstrate that the Ukrainian labour market has undergone significant transformations during the war compared to peacetime. These include: 1) A notable decrease in the number of registered unemployed individuals. 2) A reduction in the proportion of unemployed individuals receiving unemployment benefits. 3) A sharp decline in the number of vacant jobs and employers informing the State Employment Service (SES) about available vacancies. 4) A high burden on vacant jobs. It can be posited that there was a considerable surplus of labour and considerable tension in the registered labour market during the war.